2020
DOI: 10.1038/s41598-020-76780-1
|View full text |Cite
|
Sign up to set email alerts
|

Water warming increases aggression in a tropical fish

Abstract: Our understanding of how projected climatic warming will influence the world’s biota remains largely speculative, owing to the many ways in which it can directly and indirectly affect individual phenotypes. Its impact is expected to be especially severe in the tropics, where organisms have evolved in more physically stable conditions relative to temperate ecosystems. Lake Tanganyika (eastern Africa) is one ecosystem experiencing rapid warming, yet our understanding of how its diverse assemblage of endemic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 118 publications
1
9
1
1
Order By: Relevance
“…The amount of restrained displays, in contrast, was comparable between mirror tests in the laboratory and in the wild, but was lower than, and not correlated with, the number of displays shown towards a live opponent. Finally, in a sophisticated laboratory study on the impact of water warming on aggression in Julidochromis ornatus (Kua et al, 2020), individuals showed more restrained displays against the mirror than overt attacks, while the opposite was the case in the present field study. Interestingly, overt attacks and restrained displays were correlated in the laboratory, while this correlation was absent in wild fish.…”
Section: Discussioncontrasting
confidence: 61%
“…The amount of restrained displays, in contrast, was comparable between mirror tests in the laboratory and in the wild, but was lower than, and not correlated with, the number of displays shown towards a live opponent. Finally, in a sophisticated laboratory study on the impact of water warming on aggression in Julidochromis ornatus (Kua et al, 2020), individuals showed more restrained displays against the mirror than overt attacks, while the opposite was the case in the present field study. Interestingly, overt attacks and restrained displays were correlated in the laboratory, while this correlation was absent in wild fish.…”
Section: Discussioncontrasting
confidence: 61%
“…It could be due to the lifting of metabolic constraints on energetically costly behaviour, due to increases in metabolic rates that result in organisms operating outside their optimal thermal window, or due to neurons operating outside of their thermal range, producing maladaptive behaviour (Huey et al, 2012;Harshaw, Blumber & Alberts, 2017). For example, both dominant and subordinate Amazonian dwarf cichlids (Apistogramma agassizii) increase how often they bite at higher temperatures compared to dominant fish in control conditions (Kochhann, Campos & Val, 2015), while another cichlid, Julidochromis ornatus, also exhibits more mirror-elicited aggression in experimental high-temperature groups compared to control groups (Kua et al, 2020). Captive juvenile lemon damselfish (Pomacentrus moluccensis) exhibit short-term increases in their aggression as temperatures increase (Biro, Beckmann & Stamps, 2010;Warren et al, 2016), although this effect is not seen in juvenile Ambon damselfish (Pomacentrus amboinensis; Warren et al, 2016).…”
Section: (C) Agonistic Interactionsmentioning
confidence: 99%
“…Understanding water quality is key to understanding the health of an ecosystem [1]. Alterations to river hydrology, climate change, and nutrient loading due to anthropogenic pressure leads to the degradation of water quality and a reduction of biodiversity, fish survival, and fish growth [2][3][4]. The Mekong River is one of the world's largest tropical rivers, originating in China's Tibetan Plateau, and flows to the South China Sea [5].…”
Section: Introductionmentioning
confidence: 99%